(untitled) (International Educators Conference, 2025)
This article examines the integration of multimedia teaching technologies into vocational education, emphasizing their role in enhancing learning outcomes, fostering engagement, and preparing students for modern professional environments. Multimedia tools, including virtual reality (VR), augmented reality (AR), interactive simulations, and learning management systems (LMS), are explored as transformative resources for vocational training. The study highlights the benefits of multimedia technologies, such as personalized learning, competency-based assessments, and immersive experiences, while addressing challenges like resource accessibility, faculty training, and curriculum redesign. Recommendations are provided to ensure effective and equitable implementation of multimedia technologies, showcasing their potential to revolutionize vocational education and align it with industry needs.